Third-Order Neutral Delay Differential Equations: New Iterative Criteria for Oscillation - Osama Moaaz; Emad E. Mahmoud; Wedad R. Alharbi (Journal of Function Spaces)
This study is aimed at developing new criteria of the iterative nature to test the oscillation of neutral delay differential equations of third order. First, we obtain a new criterion for the nonexistence of the so-called Kneser solutions, using an iterative technique. Further, we use several methods to obtain different criteria, so that a larger area of the models can be covered. The examples provided strongly support the importance of the new results.